Influences of Salinity on Embryonic and Larval Development of Striped Catfish Pangasianodon hypophthalmus - Hossain, Farzana; Islam, S. M. Majharul; Ashaf-Ud-Doulah, Mohammad; Ali, Md Shaha; Islam, Md Sadiqul; Brown, Christopher; Shahjahan, Md (Frontiers in Marine Science, 2021)
Salinity intrusion in coastal areas due to climate change is alarming. In the present study, effects of salinity on embryonic and larval development of striped catfish (Pangasionodon hypophthalmus) were studied experimentally. Embryos and larvae were exposed to seven salinities (0, 2, 4, 6, 8, 10 and 12 ppt) in triplicate. A considerable survivability of embryos was recorded up to 6 ppt. Mortality of embryos significantly increased at 8 and 10 ppt, and 100% mortality was displayed within 12 h of exposure at 12 ppt. The rate of hatching was significantly reduced at 8 and 10 ppt. The 24 h LC50 value of salinity for embryo was 11.24 ppt. Different types of deformities, such as undeveloped yolk sac, elongated gastrula yolk sac, yolk sac bud etc. were highest at 10 ppt. Similar to embryo, a considerable survivability of larvae was recorded up to 6 ppt and 100% mortalities were found within 24 h of exposure at 12 ppt. The 24 h and 48 h LC50 values of salinity for larvae were 10.63 ppt and 8.48 ppt, respectively. Several types of deformities, including yolk sac ulceration, spine scoliosis, tail bent, yolk sac edema, compromised swim bladder inflation, etc. were highest at 10 ppt after 48 h of exposure. Within 24 h of exposure about 80% yolk-sac of the larvae was absorbed at 8 and 10 ppt, while 30-50% yolk-sac was absorbed at 0 to 6 ppt. Growth rates in terms of length and weight were higher at 0, 2 and 4 ppt, and moderate at 6 and 8 ppt. Overall, the current findings define the limits in order to optimize hatchery procedures for culture of this species in low saline brackish water.